2006
DOI: 10.5194/angeo-24-2931-2006
|View full text |Cite
|
Sign up to set email alerts
|

Solar cycle dependent characteristics of the equatorial blanketing E<sub><i>s</i></sub> layers and associated irregularities

Abstract: Abstract. The occurrence of blanketing type E s (E sb ) layers and associated E-region irregularities over the magnetic equatorial location of Trivandrum (8.5 • N; 77 • E; dip ∼0.5 • ) during the summer solstitial months of May, June, July and August has been investigated in detail for the period 1986-2000 to bring out the variabilities in their characteristics with the solar cycle changes. The study has been made using the ionosonde and magnetometer data of Trivandrum from 1986-2000 along with the available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
27
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 29 publications
(46 reference statements)
13
27
1
Order By: Relevance
“…It is observed that the occurrence of E sb is maximum during the summer solstice of both 2007 and 2009. This is in general agreement with the earlier studies on E sb (Bhargava and Subrahmanyan, 1964;Chandra and Rastogi, 1975;Devasia, 1976;Devasia et al, 2006). 4.…”
Section: Seasonal Variation Of the E Sb Occurrencesupporting
confidence: 82%
See 4 more Smart Citations
“…It is observed that the occurrence of E sb is maximum during the summer solstice of both 2007 and 2009. This is in general agreement with the earlier studies on E sb (Bhargava and Subrahmanyan, 1964;Chandra and Rastogi, 1975;Devasia, 1976;Devasia et al, 2006). 4.…”
Section: Seasonal Variation Of the E Sb Occurrencesupporting
confidence: 82%
“…For the winter solstice (January-February, November-December) of 2009, the peak E sb occurrence is seen at around 14:00 IST. Devasia et al (2006) have shown that the E sb occurrence in the equatorial region is higher during low solar activity than that during high solar activity. Also, at Indian equatorial stations, the maximum E sb occurrence is predominantly reported during the summer solstice with a minor secondary peak during the winter solstice (Bhargava and Subrahmanyan, 1964;Devasia, 1976).…”
Section: Seasonal Variation Of the E Sb Occurrencementioning
confidence: 99%
See 3 more Smart Citations